Paper John - David Small (U.S.A Sunburst Book, 1987)
Paper John moves to a little town by the edge of the sea and makes his living folding beautiful paper flowers, birds, and boats. HE is so skilled he even makes a paper house to live in. And he is so gentle and good-natured that the townsfolk all agree he could get along with the devil himself. But when a devil comes to town, Paper John's skill and patience is put to the test as he does battle with the devil and his one devilish trick. Lively full-color paintings add to all the fun.
Keywords: Read Aloud -- Read Aloud